The Impact of Individual Performance and Network Dynamics on Bonus Income in Multi-Level Marketing in Malang City - Hertanto, Ronny Hendra; Sastra , Firda Aprilia Dewi; Poernamawatie, Fahmi; Ariyani (Research Horizon, 2025)
Bonuses in the Multi-Level Marketing (MLM) system represent the income earned by each distributor. The purpose of providing bonuses by MLM companies is to show appreciation for each member who is able to expand their network and market products. This form of appreciation is why each distributor’s income varies, as it is based on performance, achievements, profits generated, education, and closing points, which differ for each distributor. Bonus income is measured through distributor performance, including the sales amount and inviting new distributors to join Tiens. The aim of this research is to determine the factors that influence the bonus income of Tiens distributors in Malang City. This research uses a descriptive quantitative method, utilizing both primary and secondary data sources. Data were analyzed using  Structural  Equation  Modeling  (SEM)  with SmartPLS. The results show that the variables of sales performance, network/team, and understanding of the marketing plan influence the intervening variable, which is closing points, and the dependent variable, bonus income. This research has implications for the Tiens or MLM company policy in determining bonus calculations for distributors, and also measuring bonus income as a target for distributor achievement.